Proceedings of the International Conference on Special and Inclusive Education (ICSIE 2018) 2019
DOI: 10.2991/icsie-18.2019.64
|View full text |Cite
|
Sign up to set email alerts
|

Project Based Learning in Improving Critical Thinking Skill of Children with Special Needs

Abstract: Active, creative, and innovative learning can produce students who can interact and compete globally including students with special needs. Students with special needs must be able to solve learning problems with critical thinking skills. However, teachers have not used alternative learning to improve critical thinking skills. One alternative learning that teachers can use is project-based learning. In this study, the method used is a systematic literature review on a national scale. The results of the survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…The significant difference was at 0.01 level. These findings are consistent with many other studies that revealed significant impact for project based learning whether face to face or online on critical thinking skills such as (Aránguiz et al, 2020), (Alawi & Soh, 2019;Eldiva & Azizah, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The significant difference was at 0.01 level. These findings are consistent with many other studies that revealed significant impact for project based learning whether face to face or online on critical thinking skills such as (Aránguiz et al, 2020), (Alawi & Soh, 2019;Eldiva & Azizah, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…It cannot be separated from the increase in students' ability to think and be creative when teachers apply Project-based learning in the classroom. This theory is in line with the research results from [9] and [10], which prove that the application of Project-based Learning can improve students' critical thinking skills.…”
Section: Discussionsupporting
confidence: 88%
“…Problem-based learning is a learning model that is often reported to be able to improve students' critical thinking skills (Birgili, 2015;Boleng & Maasawet, 2019;Masek & Yamin, 2012;Sada et al, 2016;Sulaiman & Elnetthra, 2014). Project-based learning is another cooperative learning that is also reported to have a positive impact on the development of students' thinking skills (Eldiva & Azizah, 2019;Issa & Khataibeh, 2021;Sasson et al, 2018). Unfortunately, these two learning models are still rarely implemented in various biology lessons in schools in Indonesia.…”
Section: Resultsmentioning
confidence: 99%